2016
DOI: 10.1080/03004279.2016.1250801
|View full text |Cite
|
Sign up to set email alerts
|

Exploring connections between creative thinking and higher attaining writing

Abstract: Do w nlo a d e d fro m: h t t p://i n si g h t. c u m b ri a. a c. u k/i d/ e p ri n t/ 2 5 1 5/ U s a g e o f a n y i t e m s f r o m t h e U n i v e r s i t y o f C u m b r i a' s i n s t i t u t i o n a l r e p o s i t o r y 'I n s i g h t' m u s t c o n f o r m t o t h e f o l l o w i n g f a i r u s a g e g u i d e l i n e s .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this study, it was revealed that the children showed diversity in their writing assignments including presentation through sewing, photography, and drama. While there were only two papers in this particular theme, their findings are supported by systematic reviews (Graham et al, 2012;Slavin et al, 2019) that emphasise not only new ways of exploring a range of concepts for learning but also the creation of motivating environments for improving writing (Copping, 2018). In addition to the significance of positive and encouraging learning environments, these two studies suggest that setting 'high expectations' or 'challenging experiences' are conducive to creative thinking however, teachers would need to set appropriate, reflexive conditions for this to occur.…”
Section: Creative Thinkingmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, it was revealed that the children showed diversity in their writing assignments including presentation through sewing, photography, and drama. While there were only two papers in this particular theme, their findings are supported by systematic reviews (Graham et al, 2012;Slavin et al, 2019) that emphasise not only new ways of exploring a range of concepts for learning but also the creation of motivating environments for improving writing (Copping, 2018). In addition to the significance of positive and encouraging learning environments, these two studies suggest that setting 'high expectations' or 'challenging experiences' are conducive to creative thinking however, teachers would need to set appropriate, reflexive conditions for this to occur.…”
Section: Creative Thinkingmentioning
confidence: 90%
“…We identified two articles that were focussed on creative thinking and its contribution to writing (Copping, 2018;Cress & Holm, 2016). Copping (2018) explored writing pedagogy and the connections between children's creative thinking, or a 'new way of looking at something' (p. 309), and their writing achievement. The study involved two primary schools in Lancashire, one in an affluent area and one in an underprivileged area.…”
Section: Creative Thinkingmentioning
confidence: 99%